2013
DOI: 10.7287/peerj.preprints.12v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Screening level mixture risk assessment of pharmaceuticals in STP effluents

Abstract: We modeled the ecotoxicological risks of the pharmaceutical mixtures emitted from STP effluents into the environment. The classic mixture toxicity concept of Concentration Addition was used to calculate the total expected risk of the analytically determined mixtures, compare the expected impact of seven effluent streams and pinpoint the most sensitive group of species. The risk quotient of a single, randomly selected pharmaceutical is often more than a factor of 1 000 lower than the mixture risk, clearly indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…There was also evidence to suggest that predicted mixture risks can be attributed to relatively few compounds in many cases. The latter has been observed more frequently based on measured environmental concentrations (e.g., Backhaus and Karlsson ; Vallotton and Price ). One of the common characteristics of mixture risk assessments is a difference in the availability of ecotoxicity data for the compounds involved in causing the potential risk.…”
Section: Main Findingsmentioning
confidence: 83%
“…There was also evidence to suggest that predicted mixture risks can be attributed to relatively few compounds in many cases. The latter has been observed more frequently based on measured environmental concentrations (e.g., Backhaus and Karlsson ; Vallotton and Price ). One of the common characteristics of mixture risk assessments is a difference in the availability of ecotoxicity data for the compounds involved in causing the potential risk.…”
Section: Main Findingsmentioning
confidence: 83%
“…The results of recent analyses of monitoring data provide some additional insights that are relevant for practice. That is, although the studies show that mixture impacts are important, they also show that frequently some chemicals have a relatively dominant role (e.g., [15,[29][30][31]). This was also found in scenario studies [32].…”
Section: Calibration Of Predicted Chemical Pollution Impacts To Obsermentioning
confidence: 99%
“…The hazard of chemical mixtures can be assessed by testing the whole mixturebearing in mind that it is not feasible to test all possible combinations of chemicals in mixturesor based on the concentration and effect information of the individual components of the mixture. One of the main challenges in the toxicological assessment of mixtures is the need to address data gaps: whole mixture effect data are available for a limited number of mixtures only, and single chemical hazard, dose-response, and Mode of Action (MoA) information needed in component-based approaches is often lacking for many chemical classes (Backhaus and Karlsson 2014;Evans et al 2015;Bopp et al 2016Bopp et al , 2018a.…”
Section: Challenges In the Hazard Assessment Of Mixturesmentioning
confidence: 99%
“…Using the MCR, the "nature of concern" of a mixture and related risk management actions can be decided on (Section 5.1). A review of case studies ) showed that the MCR was usually ranging between 1.2 and 5.8, depending on the number of analyzed compounds Backhaus and Karlsson 2014;De Brouwere et al 2014;Price et al 2014), that is, the number of chemicals that drive the mixture risk is usually low. In all the examples, the MCR decreased with increasing HI, indicating that the higher the predicted risk, the lower the number of substantially contributing chemicals.…”
Section: Prioritizing Mixtures and Identifying Drivers Of Mixture Riskmentioning
confidence: 99%
See 1 more Smart Citation